การศึกษาหาความสัมพันธ์ระหว่างเภสัชจลนศาสตร์ของไมโคฟิโนลิคอะซิดและผลการรักษาในผู้ป่วยโรคไตอักเสบเอสแอลอีที่ได้รับยาไมโคฟีโนเลท - พวงผกา เลิศดำรงค์ลักษณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Background: Fixed-dose (2 grams/day) of mycophenolate mofetil (MMF) is recommended for treatment of lupus nephritis. Area under the plasma concentration-time curve (AUC) of mycophenolic acid (MPA) is correlated with its efficacy in kidney transplant recipients. We determined the correlation between MPA-AUC and 6 month outcomes with mycophenolate regimen in class III / IV lupus nephritis. Methods: In this 6-month study, Twenty patients with biopsy-proven class III / IV lupus nephritis were treated with MMF (CellCept) (1-1.5 gram/day; n=14) or mycophenolate sodium (Myfortic: MPS) (1,080-1,440 mg/day; n=6). Plasma MPA AUC was measured (EMIT method) after the first month of treatment and calculated based on eight-point sampling (time 0, 0.5, 1, 2, 3, 4, 8, and 12 hours). Assessment of outcomes included changes in 24 hour urine protein excretion (UPE), estimated glomerular filtration rates (eGFR), histological activity index (AI) and clinical response (responders) defined as 50 percent reduction of urine protein or its level less than 2 g/24 hr, and normal renal function. Results: There were no correlations between MPA AUC and changes in 24 hour UPE, eGFR and histological AI after 6 months of mycophenolate treatment. However, the MPA-AUC of the responders was significantly higher than that of the non-responders (mean +/- SD 65.98 +/- 23.77 versus 32.08 +/- 7.97 h*mg/L; p = 0.002). The MPA-AUC of >60, 30-60, and < 30 h*mg/L had response rates of 100, 60 and 0 percent, respectively (p= 0.019). No correlation between drug dosage and MPA-AUC was found. In MMF group, MPA-AUC was tightly correlated with its concentration at 1 hour post-dose (r =0.925, p < 0.001) whereas no such correlation was found in MPS group. Conclusions: MPA AUC was not associated with changes in UPE, renal function and renal histology, whereas MPA AUC was correlated with therapeutic responses. MPA concentration at 1 hour post-dose was the best indicator of MPA-AUC for MMF.